2014
DOI: 10.1002/2014gl059582
|View full text |Cite
|
Sign up to set email alerts
|

M-I coupling scales and energy dumping

Abstract: The paper reviews three magnetosphere-ionosphere coupling scales characterizing (1) inverted-V auroral arcs, (2) so-called Alfvénic arcs, and (3) dense plasma clouds artificially injected into the magnetosphere. The three scale-breaking processes are different but follow all from the principle of perfect matching of the wave impedance of the energy and momentum carrier with the effective resistance of the energy dump. As a consequence, wave reflections from the ionosphere are absent or present only in a short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Some of the recent theoretical studies [e.g., Haerendel , ] also seem to suggest difference in acceleration altitude between the two types of aurora. Unfortunately, this conjecture has not been supported firmly by previous satellite/rocket observations.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the recent theoretical studies [e.g., Haerendel , ] also seem to suggest difference in acceleration altitude between the two types of aurora. Unfortunately, this conjecture has not been supported firmly by previous satellite/rocket observations.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [] showed that ionospheric irregularities can lead to field rotation of Alfvén waves, by which the coplanarity assumption mentioned above breaks down. Haerendel [] suggested that scale breaking of Alfvén waves results in maximum transport of energy from the magnetosphere to the ionosphere: so‐called self‐adjustment between Alfvénic and ionospheric conductance. According to Shi et al [], not only normal ionospheric reflection but also electron/wave interactions can affect Alfvén waves.…”
Section: Introductionmentioning
confidence: 99%
“…The principle behind scale-breaking is the optimization of the energy dumping into the ionosphere (see Haerendel, 2014). This energy resides in the magnetic tensions acquired by the initial reflections at the ionosphere.…”
Section: Magnetosphere-ionosphere Couplingmentioning
confidence: 99%